Assessing Corporate and Digital Culture to Develop Transformation Initiatives at PT SMI (SOE in Indonesia) - Citra Dutika Anindhita (Green Publisher Indonesia, 2025)
In Indonesia’s accelerating digital transformation and infrastructure development, state-owned enterprises face challenges aligning capabilities with national priorities. This research examines the alignment of organizational culture, digital maturity, and transformational strategy at PT Sarana Multi Infrastruktur (Persero) (“PT SMI”), a Special Mission Vehicle under the Ministry of Finance. As PT SMI transitions into a Development Financial Institution (DFI), it aims to improve internal agility, innovation, and cultural alignment. Using a mixed-method approach, the study maps current and preferred cultural profiles with the Organizational Culture Assessment Instrument (OCAI), assesses digital maturity via the Buvat model, and evaluates employee readiness using the ADKAR model. Results indicate a shift towards a Clan culture, contrasting with the current risk-averse Hierarchical culture. The digital maturity assessment reveals moderate progress, with strengths in data-driven decision-making but weaknesses in innovation and customer focus. The ADKAR model highlights low Awareness and Reinforcement scores, signaling transformation challenges. Thematic analysis uncovers rigid decision-making and siloed operations limiting agility. Triangulation with literature emphasizes the need for cultural realignment and better communication. A 12-month implementation plan includes phases of awareness, engagement, activation, and reinforcement, incorporating initiatives such as Change Agent Programs and digital bootcamps. This study contributes academically by connecting culture, leadership, and transformation readiness, while providing PT SMI a practical roadmap for sustainable change—offering insights applicable to other state-owned enterprises.